Endometrioid carcinomas with sex cord-like formations and hyalinization: spontaneous pregnancy after conservative treatment - Qujia Gama; Shuhan Luo; Pengfei Wu; Lulu Wang; Sijia Liu; Hongwei Zhang; Li Sun; Yiqin Wang; Min Yu; Xiaojun Chen; Weiwei Shan; Xuezhen Luo (BMC, 2024)
Abstract Endometrioid carcinoma with sex cord-like formations and hyalinization of the uterine corpus, or corded and hyalinized endometrioid adenocarcinoma (CHEC), is a rare morphological variant of endometrioid carcinoma, for which there is limited literature and few cases reports. Most researchers tend to consider CHEC as a low-grade cancer with a favorable prognosis. Full-staging surgery is the primary choice for this disease, and no case of CHEC has been previously reported to be treated conservatively. Here, we present the following case to explore the possibility of fertility-preserving treatment for young women with CHEC. A 23-year-old nulliparous patient diagnosed with presumed stage IA CHEC received fertility-sparing treatment at the Obstetrics and Gynecology Hospital of Fudan University and got a complete response (CR) after 10 months of conservative treatment. The patient subsequently became pregnant spontaneously, successfully conceived, and gave birth to a healthy male neonate without any sign of recurrence during 37 months follow-up after CR. The patient's postpartum follow-up is continuing. Presently, CHEC is not included in the fertility-sparing field of any available guidelines. This case indicates that fertility-sparing treatment may be an option for highly selected patients with CHEC. Continuous follow-up remains mandatory to observe long-term outcomes.